Video-Assisted Thoracoscopic Lobectomy Versus Stereotactic Body Radiotherapy Treatment for Early-Stage Non-Small Cell Lung Cancer: A Propensity Score-Matching Analysis - Dong, Baiqiang; Zhu, Xuan; Shu, Zekai; Ji, Yongling; Lu, Fangxiao; Wang, Jin; Chen, Ming (Frontiers in Oncology, 2020)
Objective: Video-assisted thoracoscopic surgery (VATS) lobectomy has gained popularity in early-stage non-small cell lung cancer (NSCLC). For high-risk patients who are deemed unsuitable for surgery, stereotactic body radiotherapy (SBRT) provides a potentially curative alternative. We compared the overall outcomes of VATS lobectomy versus SBRT for stage I-II NSCLC. Methods: We retrospectively compared overall survival (OS), cancer-specific survival (CSS), locoregional control (LRC), and disease-free survival (DFS) at our institution between January 2012 and December 2016. Propensity score-matching was performed to reduce patient selection bias based on age, gender, Karnofsky performance score, Charlson comorbidity index, pulmonary function, and tumor diameter. Results: A total of 567 patients treated with SBRT (n=109) or surgery (n=458) were included. Of those, 104 patients were matched for further analyses (1:1 ratio; caliper distance: 0.1). Median follow-up was 44 months. At 3 and 5 years, overall survival was 88.6% and 79.9% for SBRT, and 94.2% and 91.6% for surgery (p=0.097). There were no differences noted in 5-year cancer-specific survival (83.7% vs. 91.6%, respectively; p=0.270). The cumulative incidence of LRC at 3 and 5 years was comparable (93.5% and 93.5% vs. 94.0% and 85.9%, respectively; p=0.621). Differences in the rates of disease-free survival at 5 years were not statistically significant (79.0% and 80.5%, respectively; p=0.624). In the SBRT group, one patient suffered from grade 3 radiation pneumonitis. In the surgery group, 10% (n=5) experienced grade ≥3 Common Terminology Criteria for Adverse Events toxicity. One patient died caused by septicemia due to severe lung infection, occurred within 30 days after surgery. Conclusions: This propensity score-matching analysis suggests that SBRT can be an alternative option to VATS lobectomy for stage I-II NSCLC.